Endohedrally doped gold nanocages: efficient catalysts for O-2 activation and CO oxidation - Manzoor, Dar; Krishnamurty, Sailaja; Pal, Sourav (Physical Chemistry Chemical Physics, 2016)
Gold nanocages are the most attractive catalytic materials as all the atoms in the cage type clusters reside on the surface, making them available for chemisorption by reacting molecules. Due to a hollow space at the center, their chemical and catalytic properties can be tuned effectively and easily by endohedral doping. While a significant experimental and theoretical understanding is currently available on the structural and electronic properties of doped gold cages, very little information is available on their reactivity and catalytic behavior. In the present work, with the help of density functional theory calculations we demonstrate that endohedral doping leads to a notable increase in the binding energy of molecular oxygen on the gold nanocages. The enhancement in the O-2 binding energy on the doped gold cages is also confirmed by a significant decrease in the Au-O and an increase in the O-O bond lengths, corroborated by a red shift (similar to 250 cm(-1)) in the O-O stretching frequency as compared to the pristine cage. Furthermore, interestingly, the doped gold cages show very low activation barriers for the environmentally important CO oxidation reaction as compared to the pristine gold cage. Importantly, the decrease in the barrier height is comparatively greater for the rate limiting step of O-O-C-O intermediate formation and as a result the CO oxidation is expected to be more facile on the doped gold cages. Thus, the current study highlights the role of heteroatom doping in imparting new chemical and catalytic properties to gold cages and is expected to spur further research in the design of efficient gold nanocatalysts.